Evaluation of platelet augmentation activity of adhatoda vasica and alkaloid fraction in cyclophosphamide induced thrombocytopenic rats - SANAYE MRINAL; DALWAI ZEBA (International Journal of Pharma and Bio Sciences, 2018)
Thrombocytopenia is a haematological feature associated with varied clinical conditions. Herb Adhatoda vasica (AV) has been reported in ayurveda for treatment of blood disorders and bleeding conditions and hence was selected to explore platelet augmenting activity. Quinazoline alkaloid vasicine present in AV possess array of medicinal properties and hence was quantified in chloroform (CEAV), methanol (MEAV), petroleum ether (PEAV) and hydro alcohol extracts (HEAV) using HPTLC. Among four different extracts, CEAV showed rich content of vasicine. Thus, alkaloid fraction (AF) was isolated from CEAV and presence of alkaloid was further confirmed by performing TLC. Thrombocytopenia was induced by administering cyclophosphamide (CPX) (50mg/kg, s.c) in wistar rats (180-230 gm) of either sex. CEAV (200 and 400 mg/kg daily) and AF (60 mg/kg daily) were administered orally to CPX induced thrombocytopenic rats for a period of 15 days. Complete blood count was monitored on 4th, 7th, 11th and 15th day of treatment. Bleeding and clotting time were determined on 15th day of treatment. CEAV and AF treatment significantly (pË‚0.0001) enhanced the platelet count and also attenuated prolonged bleeding and clotting time. CPX induced neutropenia and leukopenia were reversed on treatment with CEAV and AF. Levels of inflammatory markers TNF-α and IL-6 in serum were significantly decreased as compared to toxicant. Thus, the present study demonstrated platelet augmentation effect of AV. These observed effects might be due to immunomodulatory and anti inflammatory potentials of high content of vasicine found to be present in CEAV extract.